High nonlinear optical anisotropy of urea nanofibers - Isakov, D. V. (2010)
Nanofibers consisting of the optically nonlinear organic molecule urea embedded in both poly(ethylene oxide) (PEO) and poly(vinyl alcohol) (PVA) polymers were produced by the electrospinning technique. The second-harmonic generation produced by aligned fiber mats of these materials displays a strong dependence on the polarization of the incident light. In PVA-urea nanofibers the effectiveness in generating of the second-harmonic light is as high as that of a pure urea powder with an average grain size of 110 μm. The results suggest that single crystalline urea nanofibers were achieved with a long-range crystalline order extending into the range of 2–4 μm with PVA as the host polymer.